The transformation of digital innovative services in retail trade due to the COVID-19 pandemic: A systematic review - Vaida Mardosaitė; Edmundas Jasinskas; Giedrius Romeika (Amfiteatru Economic, 2024)
Retailers should prioritise technological innovations, adapt their business models, manage their distribution channels effectively, and strengthen their customer-centric strategies. Additionally, it is crucial to note that while smart retail is gaining prominence in the sector, challenges such as the lack of digital culture, training, and digital leadership persist. The importance of digitalisation was significantly highlighted during the crisis period, which proved to be a key opportunity and solution for retailers. Before the pandemic, there was already a steady growth in retail innovations through the use of artificial intelligence (AI), the Internet of Things (IoT), and Robotics to manage data and ensure efficiencies. However, the crisis not only negatively affected retail trade (restrictions, etc.), but opened new opportunities to react faster and make good decisions when opening or improving electronic stores and implementing digital innovative solutions. Retailers' investments in digital innovation benefit their business models and improve the shopping experience for consumers.
Keywords: O33; L81; L86; M31; 330; artificial intelligence; COVID-19 pandemic; digital innovations in retailing; digital innovative services; digital technologies; retail trade; retailing process